The Effect of Video Education on Adolescent Compliance with Iron Tablet Supplementation: A Quasi-Experimental Study - Losu, Fredrika Nancy; Lumy, Freike S.N; Solang, Sisca D.; Novitasari, Anis (Public Health and Safety International Journal, 2025)
Iron deficiency anemia is a major health concern among adolescents, yet compliance with iron supplementation remains low. This study assessed the level of adolescent compliance in consuming iron tablets after video-based education, compared to conventional methods. A quasi-experimental study with a nonequivalent control group design was conducted at SMP Negeri 13 Manado. The independent variable was video-based education, while the dependent variable was compliance with iron tablet consumption. Participants were 60 adolescent girls selected through purposive sampling based on inclusion criteria (aged 12–15 years, diagnosed with anemia, and willing to participate). The experimental group (n=30) received weekly iron tablets and a video intervention, while the control group (n=30) received only iron tablets. Compliance was measured using self-reported questionnaires, observation checklists, and pill counts. Data were analyzed using bivariate analysis. This study found that while iron supplementation significantly improved hemoglobin levels in both the video intervention and control groups (p=0.0001), the educational video did not enhance compliance rates compared to standard care (p=0.754). The experimental group showed a mean hemoglobin increase of 1.51 g/dL versus 1.59 g/dL in controls, suggesting comparable biological efficacy regardless of educational approach. The study demonstrated that iron supplementation effectively increased hemoglobin levels in adolescents, but video-based education did not significantly improve compliance compared to standard care.